Céos: a collaborative web-based application for improving teaching-learning strategies - Tenório, Marcos Mincov (2018)
This paper reports the Ceos system to support and promote collaborative learning by gamification strategies and mobile technologies. C´eos was developed for basic smartphones to support classroom exercises and to encourage students out of classrooms in poor communities. The machinery of C´eos has built-in teaching-learning strategies, such as gamification and mobile learning. To evidence a new kind of active learning process, C´eos can track and suggest tips and rewards, guiding students in their decisions during the collective process of knowledge acquisition. The student knowledge acquisition also happens via C´eos during contribution of teachers, other students, and teammates. Considering the Declaration of Helsinki, an experimental research was carried out with students of a high school in the southwest of Paran´a/Brazil. We produced an experimental study to observe students social interaction behavior during a survey test using C´eos. The results indicated positive behavioral patterns, guiding them to a forum to complete the exercises. C´eos provided a friendly educational environment and automatically promoted the collaborative process of knowledge construction by the use of gamification and decision making. This collaboration between C´eos and students offered another point of view of using mobile technologies in teaching classrooms.